2015
DOI: 10.1108/lhtn-10-2014-0088
|View full text |Cite
|
Sign up to set email alerts
|

Comparing electronic vs print book preferences between students in the social sciences, the arts and STEM

Abstract: Purpose – The purpose of this study was to determine if there were any distinct differences in e-book usage habits among students in the social sciences, technical fields and the arts. Design/methodology/approach – To complete this study, students from three different disciplinary areas were surveyed. The same nine questions were posed to each student group, with slight modifications to some questions based on the discipline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
1
Order By: Relevance
“…A joint study conducted by three universities in the United States in 2015 found a strong preference for print over ebooks among students in all three universities participating in the survey. 3 Similarly, a recent survey by Blackwell's in 2019/2020 found that three-quarters of students preferred to use physical books over ebooks for their studies. The survey of 741 students across UK universities asked respondents: 'If each of the following resourcesprinted textbooks, ebooks or digital coursewareis made available to you free of charge, which would you prefer to use in your studies?'…”
Section: Impact Of Covid-19 On Studentsmentioning
confidence: 99%
“…A joint study conducted by three universities in the United States in 2015 found a strong preference for print over ebooks among students in all three universities participating in the survey. 3 Similarly, a recent survey by Blackwell's in 2019/2020 found that three-quarters of students preferred to use physical books over ebooks for their studies. The survey of 741 students across UK universities asked respondents: 'If each of the following resourcesprinted textbooks, ebooks or digital coursewareis made available to you free of charge, which would you prefer to use in your studies?'…”
Section: Impact Of Covid-19 On Studentsmentioning
confidence: 99%
“…Namun demikian, untuk memperjelas penggunaannya perlu ditambah video tutorial agar dapat dimanfatkan lebih optimal. Menurut Cummings (2015), perpustakaan membutuhkan berbagai upaya untuk meyakinkan mahasiswa agar paham dan memberikan bimbingan cara untuk mengaksesnya.…”
Section: Kebutuhan Pelatihan Menggunakan Fitur Buku Teks Elektronikunclassified
“…In a survey conducted in e-book usage habits among students in the social sciences, technical fields, and the arts at Binghamton University, Cummings, and colleagues found print still had many advantages over electronic format in terms of how scholars used the material including visibility of images, ease of navigation, and note taking. Although there are still a large percentage of students across disciplines who prefer print, data from this study indicated that many students were willing to adapt to the e-book option (1). A University of Pittsburg survey found library e-books were used by 55.4% of respondents.…”
Section: Introductionmentioning
confidence: 95%